Factors contributing to the Success of Aquaculture Field Schools - Saha, Gour Sundar; De, Himansu Kumar; Mahapatra, Abhijit Sinha; Panda, Nirupama (Journal of Extension Education, 2020)
ICAR- Central Institute of Freshwater Aquaculture (CIFA) had piloted four Aquaculture Field Schools (AFS), a model of farmer to farmer extension, in Odisha and Chhattisgarh states in India. The AFS’ are attracting farmers and stakeholders as they provide a platform to share experience and enable cross learning. In this research, an attempt has been made to identify the factors that contribute to the successful performance of AFS. Data were collected from 166 user farmers, selected randomly from the list available with operators. Five variables viz., age of fish farmer, frequency of visit to AFS, duration of visit, interaction with the fellow farmers and advocation of advanced technologies of ICAR-CIFA to other farmers were observed to be significantly contributing to yield of fish. The Multiple correlation coefficient, R=0.48, indicated that there is a significant and positive correlation between the observed and predicted value of fish yield.